ACTIVE STRIDES-CP: protocol for a randomised trial of intensive rehabilitation (combined intensive gait and cycling training) for children with moderate-to-severe bilateral cerebral palsy - Robert S Ware; Roslyn N Boyd; Stewart Trost; Mark D Peterson; Leanne Sakzewski; Iona Novak; Catherine Elliott; Sian Williams; Tracy Comans; Jane Valentine; Sarah Elizabeth Reedman; Rachel Toovey; et al. (BMJ Open, 2023)
Introduction For children with cerebral palsy (CP), who are marginally ambulant, gross motor capacity peaks between 6 and 7 years of age with a subsequent clinical decline, impacting their ability to engage in physical activity. Active Strides-CP is a novel package of physiotherapy targeting body functions, activity and participation outcomes for children with bilateral CP. This study will compare Active Strides-CP to usual care in a multisite randomised waitlist-controlled trial.Methods and analysis 150 children with bilateral CP (5–15 years), classified in Gross Motor Function Classification System (GMFCS) levels III and IV will be stratified (GMFCS III vs IV, age 5–10 years; 11–15 years and trial site) and randomised to receive either (1) 8 weeks of Active Strides-CP two times/week for 1.5 hours in clinic and one time/week for 1 hour alternating home visits and telehealth (total dose=32 hours) or (2) usual care. Active Strides-CP comprises functional electrical stimulation cycling, partial body weight support treadmill training, overground walking, adapted community cycling and goal-directed training. Outcomes will be measured at baseline, immediately post-intervention at 9 weeks primary endpoint and at 26 weeks post-baseline for retention. The primary outcome is the Gross Motor Function Measure-66. Secondary outcomes include habitual physical activity, cardiorespiratory fitness, walking speed and distance, frequency/involvement of community participation, mobility, goal attainment and quality of life. Analyses will follow standard principles for randomised controlled trials using two-group comparisons on all participants on an intention-to-treat basis. Comparisons between groups for primary and secondary outcomes will be conducted using regression models. A within-trial cost utility analysis will be performed.Ethics and dissemination The Children’s Health Queensland Hospital and Health Service, The University of Queensland, The University of Melbourne and Curtin University Human Research Ethics Committees have approved this study. Results will be disseminated as conference abstracts and presentations, peer-reviewed articles in scientific journals, and institution newsletters and media releases.Trial registration number ACTRN12621001133820.